Applying decision research to improve clinical outcomes, psychological assessment, and clinical prediction - Gaudet, Charles E.; Arkes, Hal R. 1945-; Faust, David 1952- (Oxford University Press, 2024)
"A client facing very difficult circumstances develops suicidal ideation and comes to you, their therapist, for help. Your immediate tasks are to ascertain the risk of suicide and to intervene as needed. Suppose the client is facing a challenging and troubling situation at work that could go very wrong. The client has a history of sexual abuse and intermittent loss of anger control, although her self-control has improved considerably as treatment has progressed. The client works at a small, family-owned company. Her boss, although usually supportive, has made a number of insensitive comments. These comments have triggered powerful emotional reactions and thoughts of self-destructive actions. The client, who desperately needs the job but finds the situation intolerable, has made a firm decision to talk with her boss. The concern is that the boss will respond badly, the client in turn will respond with uncontrolled anger, and things will go downhill rapidly from there, potentially eventuating in a suicide attempt"-- Provided by publisher.